KARAKTER MORFOLOGIS KULTIVAR SALAK (Salacca edulis Reinw.) JANTAN DAN BETINA DI KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - , NUR FITRIANA ARIYANTI, Rina Sri Kasiamdari, S. Si., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research about characters variation, morphological character, and phenetic relationship of snakes fruit cultivar (Salacca edulis Reinw.) at Sleman was focused on female plant relationship. The objective of the research was to study the morphological character comparation and phenetic relationship of male and female snakes fruits cultivar, and to know the principal characters that play an important role in the grouping. Samples of 23 individu from pondoh hitam, pondoh super, manggala, madu soka, jawa, gading dan male plant was conducted at four subdistricts at Sleman, there were Purwobinangun, Candibinangun, Donokerto, and Girikerto. Observations of morphological character was done in the qualitative and quantitative characters at leaves and flower organs. Selected characters were scored and coded according to the âmulti-state charactersâ rules. Similarity index value was calculated by assosiation correlation with Gower General Similarity Coefficient. Standarization, dendogram construction and principal component were analyzed with MVSP (Multi-Variate Statistical Package) 3.13n software. Results showed that the main morphological character comparation of male and female plant were pistil and fertile stamen present. Based on the dendogram construction, there were two-main groups, male plant and female plant with 54,2% index similarity value. The highest index similarity value was owned by female gading Purwobinangun and female gading Candibinangun with 85,5%. The principal characters that played an important role in the grouping were pistil protective fiber color (axis 1= -0.225